KLEMS growth accounting implemented in Poland - Dariusz Kotlewski; Mirosław Błażej (Statistics in Transition New Series, 2020)
The aim of the article is to present the main body of the KLEMS growth accounting recently implemented in Poland. The works on the KLEMS productivity accounting in Poland started in 2013 and focused on areas such as the development of methodology and the availability and assessment of data. These efforts enabled preparing KLEMS data sets pertaining to the Polish economy and moreover proved that unavailable data can be effectively estimated. Additionally, interesting but complex and debatable results were obtained, such as labour hoarding together with remunerations' freezing around the 2009 crisis, accompanied by a natural drop in the capital contribution growth and an increase in the MFP contribution, which most probably indicated effective reorganizations in the economy. In the years 2012−2014, increasing labour and capital contributions did not fully translate into gross value added growth, which led to negative MFP growths, as these are calculated residually. This, however, changed completely in the last two years of the time span covered by the research, namely in 2015-2016. An industry-level analysis became also possible, showing that the Polish economy was developing dynamically and undergoing intensive modernisation, which was obtained, however, with a debatable contribution of the State. To study the debatable features of the Polish economy in a greater detail, a further decomposition of the labour factor growth into four sub-factor contributions instead of two sub-factor contributions was performed. This additional analysis confirmed that labour hoarding phenomenon specific for Poland contributed to a softer impact of the 2007−09 financial crisis on this country's economy.
Keywords: 519; gross value added; decomposition; production factors; KLEMS; productivity